Differentiation of Human Mesenchymal Stem Cell into Chonderocyte Like Cells 3D Poly Lactic Acid Glycosaminoglycan (PCL-GAG) Nano Fibre Scaffold - Maryam Sahlolbei; Masoud Solemani; Nematollah Razmi; Naser Amirizadeh (Negah Institute for Scientific Communication, 2013)
Introduction: Failure of human body tissue and organs is believed to be one of the most important health problems all over the world. The great challenge for tissue engineers is to optimize suitable systems to separate, proliferate and differentiate the cells so that they can set out to create tissue by a harmonic 3-D growth. Therefore, the tissue engineers must provide an environment like the living cells environment. Methods: In this study, to increase efficiency, the nano fiber structure of poly lactic acid modified with glycosaminoglycan. Then the mesenchymal cells of bone marrow cultured on this 3-D structure with differentiated media culture of TGF-ß .To investigate differentiation, the genes expressed in cartilages tissue were used containing collagen gene, aggrecan and SOX9. The expression of gene confirmed by quality method of Reverse Transcriptase PCR then quantitatively examined by Real -Time PCR. Results: The finding showed that using nano fiber scaffold of poly lactic acid modified with glycosaminoglycan leads to the increase of expression of cartilage gene. Conclusion: Our findings indicated that GAG/PCL Nano fiber scaffold enhances the differentiation of mesenchymal stem cells into cartilage.This can help to overcome the limitations of tissue engineering.